ABCC6 Knockdown Fuels Cell Proliferation by Regulating PPARα in Hepatocellular Carcinoma - Zhao, Zhicong; Zhao, Zhenjun; Wang, Jianye; Zhang, He; Xi, Zhifeng; Xia, Qiang (Frontiers in Oncology, 2022)
The ATP binding cassette (ABC) transporter family is ubiquitous in eukaryotes, specifically in vertebrates, and plays a crucial role in energy homeostasis, cell signaling, and drug resistance. Accumulating evidence indicates that some ABC transporters contribute to cancer cell proliferation and tumor progression; however, relatively little is known about the behavior of the ABC transporter family in hepatocellular carcinoma (HCC). By analyzing two public transcriptomic databases, we evaluated the effect of genes in the ABC transporter family on HCC prognostic prediction; ABCC6 was selected for further study. Notably, ABCC6 was found to be downregulated in HCC tissues and correlated with favorable outcomes in patients with HCC. Moreover, ABCC6 knockdown not only significantly promoted cell proliferation in vitro and in vivo, but also inhibited cell cycle arrest and cell apoptosis. Transcriptome analysis revealed that ABCC6 depletion enhanced the “mitotic cell cycle” and “DNA replication” pathways, and suppressed the “PPAR signaling pathway”. Further investigation demonstrated that PPARα, one of the key regulators in peroxisome metabolism, is located downstream of ABCC6. In summary, our study provides profound insights into the behavior of ABC transporter family genes in various HCC cohorts, identifies ABCC6 as a biomarker for early-stage HCC diagnosis, and offers experimental basis for further investigations of targeting ABCC6 in the treatment of patients with HCC.